To simplify the expression, we distribute the -12 across the terms in the parentheses:
-12(b+2) + 3b = -12*b - 12*2 + 3b
Simplifying further:
=-12b - 24 + 3b
Now, we combine like terms:
= -9b - 24
Thus, the simplified expression is -9b - 24.
Simplify.
−12(b+2)+3b
9 answers
Simplify.
−1/2(b+2)+3b
−1/2(b+2)+3b
To simplify the expression, we distribute the -1/2 across the terms in the parentheses:
-1/2(b+2) + 3b = (-1/2*b) + (-1/2*2) + 3b
Simplifying further:
= -1/2b - 1 + 3b
Now, we combine like terms:
= (3b - 1/2b) - 1
Now, we find a common denominator and combine the fractions:
=(6b - 1)/(2b) - 1
= (6b - 1 - 2b)/(2b)
= (6b - 2b - 1)/(2b)
= (4b - 1)/(2b)
Thus, the simplified expression is (4b - 1)/(2b).
-1/2(b+2) + 3b = (-1/2*b) + (-1/2*2) + 3b
Simplifying further:
= -1/2b - 1 + 3b
Now, we combine like terms:
= (3b - 1/2b) - 1
Now, we find a common denominator and combine the fractions:
=(6b - 1)/(2b) - 1
= (6b - 1 - 2b)/(2b)
= (6b - 2b - 1)/(2b)
= (4b - 1)/(2b)
Thus, the simplified expression is (4b - 1)/(2b).
Simplify.
−1/2(b+2)+3b
Responses
5/2b−1
fraction 5 over 2 end fraction b minus 1
7/2b+1
fraction 7 over 2 end fraction b plus 1
5/2b+2
−1/2(b+2)+3b
Responses
5/2b−1
fraction 5 over 2 end fraction b minus 1
7/2b+1
fraction 7 over 2 end fraction b plus 1
5/2b+2
To simplify the expression, we distribute the -1/2 across the terms in the parentheses:
-1/2(b+2) + 3b = (-1/2*b) + (-1/2*2) + 3b
Simplifying further:
= -1/2b - 1 + 3b
Now, we can combine like terms:
= (3b - 1/2b) - 1
Now let's find a common denominator and combine the fractions:
= (6b - 1)/(2b) - 1
= (6b - 1 - 2b)/(2b)
= (4b - 1)/(2b)
Therefore, the simplified expression is (4b - 1)/(2b).
-1/2(b+2) + 3b = (-1/2*b) + (-1/2*2) + 3b
Simplifying further:
= -1/2b - 1 + 3b
Now, we can combine like terms:
= (3b - 1/2b) - 1
Now let's find a common denominator and combine the fractions:
= (6b - 1)/(2b) - 1
= (6b - 1 - 2b)/(2b)
= (4b - 1)/(2b)
Therefore, the simplified expression is (4b - 1)/(2b).
Which property is demonstrated?
(4+x)+2y=4+(x+2y)
Responses
Commutative property of addition
Commutative property of addition
Associative property of addition
Associative property of addition
Distributive property
Distributive property
I don't know.
(4+x)+2y=4+(x+2y)
Responses
Commutative property of addition
Commutative property of addition
Associative property of addition
Associative property of addition
Distributive property
Distributive property
I don't know.
The property demonstrated in the given equation is the associative property of addition. This property states that, when adding or subtracting multiple numbers, the grouping of the numbers can be changed without affecting the result. In this case, the grouping of (4+x) and 2y is changed to (x+2y), showing the associative property of addition.
Which expression represents this phrase?
8 less than the quotient of 5 and a number
Responses
5/n−8
fraction 5 over n end fraction minus 8
n/5−8
fraction n over 5 end fraction minus 8
8−5/n
8 minus fraction 5 over n
I don't know.
8 less than the quotient of 5 and a number
Responses
5/n−8
fraction 5 over n end fraction minus 8
n/5−8
fraction n over 5 end fraction minus 8
8−5/n
8 minus fraction 5 over n
I don't know.
The expression that represents the phrase "8 less than the quotient of 5 and a number" is 5/n - 8. This is because the quotient of 5 and a number n is represented by 5/n, and then subtracting 8 from it gives us "8 less than the quotient of 5 and a number".